(untitled) (Annals of Medical Research, 2023)
Aim: This study aimed to present the genetic, clinical, and follow-up data of our patients diagnosed with glucokinase (GCK)-MODY. Type 2 Maturity Onset Diabetes of the Young (MODY) is a monogenic disease characterized by fasting hyperglycemia resulting from impaired insulin secretion. It constitutes the vast majority of cases with monogenic diabetes. Materials and Methods: In the study, clinical, follow-up, and genetic data of 13 patients who were followed up with the diagnosis of MODY type 2 diabetes and had mutations in the GCK gene in their molecular analyses were studied. GCK whole gene sequence analysis was performed with Sanger sequencing. Results: The age at diagnosis was median 11.0 years (range: 2.5–16.9). High blood sugar was the most common reason for admission (84.6%). At the time of diagnosis, the patients’ mean blood sugar was 137.0±52.4 mg/dL, insulin 6.1±2.8 mU/L, c-peptide 1.4±0.6 ng/mL, triglyceride 106.1±42.3 mg/dL, and cholesterol 154.0±19.0 mg/dL. While HbA1c was 6.3±0.4 at the time of diagnosis, it was 6.2±0.4 at the end of the mean 5-year follow-up (p=0.073). Molecular analysis revealed the most common variant as c.565A>G (p.I189Val) (53.8%). In all cases, glucose levels were regulated by diet and exercise, and there was no need for insulin. Conclusion: Incidental blood glucose elevation was an important finding in diagnosing GCK-MODY. With the molecular diagnosis of these patients, clinical follow-ups, treatment plans, and long-term prognoses can be planned more accurately. Therefore, in doubtful cases, the genetic diagnosis should be confirmed by sequencing the GCK gene.